SATELLITE AND GROUND-BASED AIR QUALITY ASSESSMENT IN AL-DIWANIYAH - Ali S. Saleh; Alaa K. Jasim; Alaa S. Hantoosh (Antis-Publisher, 2026)
Objective: Ambient atmospheric pollution represents a critical threat to human health globally. Within Iraq, air quality has drastically diminished due to harsh climatic dust events and expanding unregulated anthropogenic factors. The primary goal of this investigation is to establish a thorough comparative analysis of air quality across the urban and rural sectors of Al-Diwaniyah Province. Method: A comparative cross-sectional design was carried out from mid-September 2025 through January 2026 across six strategic sampling locations. Ground-level monitoring utilized a calibrated Temtop M2000 device to log particulate metrics, while space-borne observations were acquired via the Sentinel-5P TROPOMI satellite for gaseous pollutants. A composite Z-score air quality index (AQI) evaluated safety thresholds, with statistical analysis processed through SPSS v26 software. Results: Ground measurements revealed that average PM2.5 (34.87 µg/m³) and PM10 (101.37 µg/m³) drastically outpaced WHO safety limits (p < 0.001). Satellite monitoring demonstrated a significant abundance in tropospheric NO₂ (63.54 µmol/m²) and O₃. The index classified 73.3% of the total observations as unhealthy for sensitive demographics. Urban sectors displayed significantly higher concentrations of PM2.5, PM10, and CO₂ than rural environments (p < 0.001), though rural locations showed a high prevalence (80.0%) of air quality categorized as hazardous for sensitive groups. Novelty: Al-Diwaniyah Province experiences severe atmospheric degradation. While urban centers undergo heavier pollution loads from concentrated traffic and fuel combustion, rural zones present distinct ambient threats to vulnerable populations from agricultural operations and dust.